Implementasi Pembelajaran Sains Dan Kecerdasan Logika Matematika Pada Anak Kelompok A TK/RA Pandanaran Karangnongko Klaten Tahun Ajaran 2016/2017 - Hirowati, Indah, Dra. Surtikanti, S.H., M.Pd (2017)
It motivated by the teacher who always used worksheet to learning, so student becomes bored, not excited and easy sleepy in the class. The purpose of this study was to descript and to find out the benefits from implementation of learning science and mathematical logic intelligence for children in group A TK/RA Pandanaran, Karangnongko, Klaten academic year 2016/2017. The research was design by used qualitative methods with description qualitative approach. The subject in this study is all student in group A TK/RA Pandanaran. Data collection techniques in this research was done with participating observation, interview and documentation. Data analysis techniques used three flows with data reduction, display and verifing. Implement learning science is able to train and develop the intelligence of mathematical logic with regard to the child's abilities in thinking, and overcoming the problems encountered, also it be able to train children to became more ability, honest, decipline and it can make enjoyable learnig for children. Learning science, Mathematical logic intelligence